COVID-19 Shock and Sectorial Index Response in South Africa: A Cross-sector Analysis - Vengesai, Edson (International Journal of Economics and Financial Issues, 2022)
The prime objective of this study was to examine the impact of COVID-19 shock on sector returns of the South African Stock market. The study employed the Autoregressive Distributed Lag (ARDL) model estimated with a Pooled Mean Group estimator on a sample of daily stock returns of 10 Johannesburg Stock Exchange (JSE) sectors. The results indicate a heterogeneous behaviour in sector stock return response to COVID-19 shock. The study shows that the Pandemic negatively impacted the majority of the sectors. However, some sectors were positively affected by the outbreak, while some were resilient to the shock. The pooled ARDL panel results show a negative relationship between COVID-19 and stock market returns in the short run. The study found an insignificant relationship between stock market returns and COVID-19 cases in the long run. The study also shows that sector and stock return response to different factors is time-varying. The results imply that COVID-19 shock is short-lived, the negative impact of the Pandemic is corrected in the long run. Stock market investors should thus focus on the long-run behaviour of stock returns. The results evidence the significance of diversification in different stock market sectors for investors